A room of one's own ebook - Woolf, Virginia (Books on Demand, 2021)
'A Room of One's Own' is considered a key work of feminist literary criticism. In it, Woolf examines the historical disempowerment women have faced in many spheres, including social, educational and financial. One of her more famous dicta is contained within the book "A woman must have money and a room of her own if she is to write fiction". Much of her argument is developed through the unsolved problems of women and fiction writing to arrive at her conclusion, although she claimed that was only an opinion upon one minor point.